Repetition, adaptation, institutionalization—How the narratives of political communities change - Johanna Hase (Ethnicities, 2021)
At times when migration and diversity are politically salient and controversially discussed, the rhetoric of staying `as we are' is widespread. But how do `we' actually change and how would `we' know when it happens? Based on the premise that political communities are the products of narratives of peoplehood, this paper explores how such narratives evolve over time. It conceptualizes different modes of balancing narrative continuity and change. These modes – repetition, adaptation, and institutionalization – are illustrated with reference to evolving German narratives of peoplehood centring around (not) being a country of immigration. The paper argues that all modes lead to some degree of change in narratives of peoplehood. Against the backdrop of different understandings of the core of a narrative, it further discusses when such changes fundamentally affect who `we' are. Overall, the paper invites scholars, policymakers, and citizens to think critically about the essential aspects of their political communities' narratives and to be aware of the stories that `we' are told and that `we' tell ourselves.
Keywords: 300; political communities; narratives of peoplehood; narrative analysis; citizenship; Germany; immigration